ANTESEDEN RISK DAN TRUST YANG MEMPENGARUHI SIKAP INDIVIDU TERHADAP NIAT ADOPSI E-BANKING - Saputro, Edy Purwo; Dihan, Fereshti Nurdiana (Benefit: Jurnal Manajemen dan Bisnis, 2011)
The e-banking adoption researches have been conducted with diversity in the approach models in which they found the model diversity so that these are casuistic. This fact becomes an interesting gap research. The purpose of this article is to provide an insight into the determinants of customersâ e-banking acceptance. The samples of the study numbered to 200 people analyzed with SEM. Results indicate that the concept of trust and risk have merit in explaining consumersâ decisions on whether to use e-banking. These findings are also related to the theoretical, practical, managerial, and methodological implications and implication to further studies although this study is limited.Â